2018
DOI: 10.1155/2018/2870503
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Velvet Antler (Cervus elaphus) against Lipopolysaccharide‐Induced Acute Lung Injury in Mice by Inhibiting MAPK/NF‐κB Activation and Inducing AMPK/Nrf2 Pathways

Abstract: Velvet antler (Cervus elaphus) is a typical traditional animal medicine. It is considered to have various pharmacological effects including stimulation of the immune system, increase in the physical strength, and enhancement of sexual function. This paper aims to investigate the aqueous extract of velvet antler (AVA) in the mouse models of LPS-induced ALI. Inhibition of NO, TNF-α, IL-1β, IL-6, and IL-10 productions contributes to the attenuation of LPS-induced lung inflammation by AVA. A 5-day pretreatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
(40 reference statements)
0
23
0
Order By: Relevance
“…In the MAPK family, a series of protein kinases, such as JNK, Erk, and p38MAPK, are involved in diverse cellular responses, including inflammation-related pathways. These MAPKs are activated by either extracellular or intracellular signals [43,44], which in turn promotes early pro-inflammatory cytokine production during the inflammatory process [45][46][47]. The MAPK signaling pathway is known to be activated in response to LPS-induced ALI [11,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In the MAPK family, a series of protein kinases, such as JNK, Erk, and p38MAPK, are involved in diverse cellular responses, including inflammation-related pathways. These MAPKs are activated by either extracellular or intracellular signals [43,44], which in turn promotes early pro-inflammatory cytokine production during the inflammatory process [45][46][47]. The MAPK signaling pathway is known to be activated in response to LPS-induced ALI [11,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK and NF‐κB are vital factors that play an essential role in adjusting inflammatory reactions by affecting the expression of numerous inflammatory cytokine genes . NF‐κB and MAPK can be stimulated by various factors, such as LPS and RIR . NF‐κB and MAPK can modulate the transcription of a great number of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, sika deer antler protein (SDAPR) can protect cisplatin‐induced and gentamicin‐induced AKI (Sun et al, ; Yang et al, ). The study also showed that antlers can resist LPS‐induced acute lung injury by activating AMPK/Nrf2 pathway (Chang et al, ). HK‐2 cell lines have been used for pharmacological experiments in vitro on kidney injury models (Vrbová, Roušarová, Brůčková, Česla, & Roušar, ).…”
Section: Introductionmentioning
confidence: 95%